A efetividade da tutela jurisdicional e o resgate do crédito fiscal - Chaves, Erika Gomes (2012)
The effectiveness of the judicial proceedings in tax enforcement is a fundamental right of the taxpayer. This is because its mission is to overcome the crisis of the failure to pay of the tax credit and thus provide effective inflow of financial resources indispensable to the implementation of fundamental rights. However, the current stage of this executive collection in Brazil is inefficient. These processes are slow, expensive and without effective results such as the increasing accumulation, inflating, negatively, the statistics of the Executive and Judiciary powers. We must therefore reflect on the problem in the search of possible solutions that can provide effective judicial protection in tax enforcement.